Traditional Knowledge of Medicinal Plants in Narayanbagar Block, Chamoli District of Garhwal Himalaya, Uttarakhand, India - Deoli, Jyoti; Yadav, Vinod Kumar; Pande, P. K. (Indian Forester, 2015)
The present study carried out in Narayanbagar block in Chamoli district of Uttarakhand in Western Himalaya to explore traditional knowledge of medicinal plants. Most of the local people depend on the forest and agriculture produce for their livelihood and daily needs. Informations on medicinal plants were collected through questionnaire survey, formal and informal interviews. Total 136 formal interviews from 22 out of 70 randomly selected villages were carried out. A total of 146 medicinally important plant species belonging 65 families were reported. Majority of collected species were herbs (73%), followed by shrubs (14%), trees (7%) ferns (3.42%) and climbers (2%). The botanical name, family, local name, parts used, and medicinal properties of collected plants documented.